Study of objects visualization and image inversion by the phase-contrast method with linear and nonlinear filters. (August 2016) - Bubis, E L; Lozhkarev, V V; Stepanov, A N; Smirnov, A I; Kuzmin, I V; Malshakova, O A; Gusev, S A; Skorokhodov, E V
Abstract: The adaptive phase-contrast method with nonlinear (photothermal) and linear Zernike filters was investigated. Liquid and polymer media partially absorbing radiation served as photothermal Zernike filters. Efficient visualization and inversion of images of small-scale model objects were demonstrated experimentally. Growth-sector boundary in a nonlinear crystal was visualized.